2021
DOI: 10.3389/fmed.2021.695195
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Severe/Critical Outcomes in Patients With SARS-CoV2 Pneumonia: Development of the prediCtion seveRe/crItical ouTcome in COVID-19 (CRITIC) Model

Abstract: Objective: To create a prediction model of the risk of severe/critical disease in patients with Coronavirus disease (COVID-19).Methods: Clinical, laboratory, and lung computed tomography (CT) severity score were collected from patients admitted for COVID-19 pneumonia and considered as independent variables for the risk of severe/critical disease in a logistic regression analysis. The discriminative properties of the variables were analyzed through the area under the receiver operating characteristic curve anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
0
7
1
Order By: Relevance
“…To better compare patients with multiple comorbidities, we employed the use of an age-excluding CCI to quantify comorbidity burden. Although previous studies have demonstrated that CCI commonly predicts survival (37)(38)(39), we demonstrate that an age-excluding CCI can also be predictive of mortality. Based on the how CCI is calculated, certain comorbidities such as diabetes and CKD are weighted more than other factors such as coronary heart disease and are predicted to have a greater influence on mortality.…”
Section: Discussioncontrasting
confidence: 88%
“…To better compare patients with multiple comorbidities, we employed the use of an age-excluding CCI to quantify comorbidity burden. Although previous studies have demonstrated that CCI commonly predicts survival (37)(38)(39), we demonstrate that an age-excluding CCI can also be predictive of mortality. Based on the how CCI is calculated, certain comorbidities such as diabetes and CKD are weighted more than other factors such as coronary heart disease and are predicted to have a greater influence on mortality.…”
Section: Discussioncontrasting
confidence: 88%
“… 48 The CCI demonstrated excellent discriminative ability, with an AUC of 0.854 (p < .001) and an optimal cut-off point of 3 (sensitivity 83.8%, specificity 69.6%, + LR 2.76). 49 Additionally, multiple studies have demonstrated SAPS-3 and NEWS-2 scoring systems as severity and mortality predictor tools of COVID-19 infection. 50 52 Despite serum KL-6 having a similar AUC to this severity assessment tool, the low sensitivity of KL-6 makes it a weaker test.…”
Section: Discussionmentioning
confidence: 99%
“…The CT severity score has an AUC of 0.824 (p < .001) and an optimal cut-off point of 53 (sensitivity 64.9%, specificity 84.4%, and PLR 4.17. 49 A study by Saeed et al suggested that the CT chest, despite having a pivotal role in severity assessment, is prone to interpreter bias. 53 However, compared with the detection of COVID-19 through chest CT and nucleic acid detection, the measurement of KL-6 levels is fast, inexpensive, noninvasive, no radiation hazard, and sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the COVID-19 pandemic has impacted profoundly on those with concomitant cardiovascular comorbidities [16], we considered whether digoxin-treated patients might be more susceptible to COVID-19 than those treated with standard of care. The reason for this consideration was that increased comorbidities, as defined by the Charlson Comorbidity Index (CCI), have been widely seen to be associated with worse outcomes for COVID-19 [17][18][19][20]. By contrast, it has been reported that digitoxin and ouabain, and with lesser potency digoxin, interfere with penetration of the SARS-CoV-2 virus into human lung cells [21] and green monkey kidney cells [22].…”
Section: Introductionmentioning
confidence: 99%